MODEL CALCULATION OF THE ELECTRON ENERGY STUCTURE OF DIAMOND, BN AND BeCN2 - A.A. LAVRENTYEV; B.V. GABRELIAN; I.Ya. NIKIFOROV (Advanced Engineering Research)
The electronic energy structure of the row of similar compounds: diamond (C), BN, and BeCN2 has been investigated. It was found for BeCN2 that the top of the valence band is formed by p-states of N, whereas the bottom of the conduction band - by s-states of Be and C. The width of the energy forbidden band Eg in BeCN2 - was estimated. The comparison of the calculated partial and total electron densities of states of diamond and BN with x-ray K-spectra of emission and absorption and with x-ray electron spectra was carried out. The corresponding partial electron states of diamond and BN were also compared with corresponding densities of states of BeCN2.